The Influence of Financial Distress, Profitability, and Firm Size on Audit Delay (An Empirical Study on Companies in the Properties and Real Estate Sub-Sector Listed on the Indonesia Stock Exchange for the Period of 2017-2021) - Rino, Rino Mauladiputro; Apollo Daito (Journal of Accounting and Finance Management, 2024)
This study aims to examine the factors that affect the audit delay in the Properties and Real Estate Sub-Sector companies listed on the Indonesia Stock Exchange for the period of 2017-2021. The factors used in this study are Financial Distress, Profitability, and Firm Size. This research is motivated by the importance of information on factors that can affect audit delay. In this study, to measure audit delay, it is measured based on the length of days needed to obtain an independent auditor's report. The population that was used as the object of observation in this study were the Properties and Real Estate Sub-Sector companies listed on the Indonesia Stock Exchange for the period 2017-2021, and a total of 65 companies were obtained. This sampling method uses a purposive sampling method, in which the method in sampling uses certain criteria. Then 34 companies were selected that met the criteria multiplied by the 5 year observation period so that the total data became 170 data. Samples were downloaded via the web http://www.idx.co.id and the type of data in this study was secondary data. The method of data analysis in this study is to use statistical calculations with the application of SPSS (Statistical Product and Service Solution). This study shows that Financial Distress and Profitability have a negative effect on Audit Delay. Meanwhile, the Firm Size variable has no significant effect on Audit Delay.